Immunopathology of alphamethrin in bovine calves - Chauhan, R S; Agrawal, D K (The Indian Journal of Animal Sciences, 2012)
Immunopathological effects of alphamethrin, a synthetic pyrethroid, was studied in 6 crossbred male bovine calves. The results showed that the blastogenic activity of T- and Î²- lymphocytes reduced 48 and 40%, respectively, in alphamethrin fed calves in comparison to controls. There was significant decrease in BoCD+â‚„ (T- cytotoxic), brucella specific antibody titres and total Ig G and Ig M titres in alphamethrin fed calves. Alphamethrin was found to have immunosuppressive effect at a dose of 5 mg/kg b w which may lead to increased susceptibility to various diseases.